Zur fluvialen Morphodynamik bei Schneeschmelz- und bei Pluvialabfluss in kleinen periglazialen Flussgebieten NW-Kanadas - Priesnitz, Kuno; Schunke, Ekkehard (ERDKUNDE, 2001)
Based on hydrological field work in the tundra of Northwest Canada during the spring of 1986, 1990, 1992 and 1994 and the summer of 1998 and 1999, the paper deals with the fluvial processes induced by spring snow-melt and summer rainfall in two small stream valleys. The valleys investigated are typical flat-bottomed valleys, the floors of which at the end of winter are covered by icings over most of their lengths. The biggest quantity of the meltwater run-off passes in an ice channel on top of the aufeis. This means on one side that most of the bed material is protected against erosion during the meltwater run-off peak, at the other side it causes a high erosion and transport potential of the nival flood, with current velocities up to 4.8 m/s. The most effective fluvial sediment transport takes place during the short run-off interval, when the aufeis has disappeared in some places. The calculated suspension transport during snow-melt flood is 62-312 t/km2 in different years. During summer base-flow and some stronger rainfall discharges do not reach by far the snow-melt current velocities and their sediment transport. In summer suspension transport runs up to 0.3-1.4 t/km2, which is less than 1 % of the snowmelt value and it is lower than the solution transport of 8-24 t/km2. Thus it is demonstrated, that the fluvial effects induced by snow-melt are much more important than those caused by summer run-off, even considering thundershowers. There are no data about the frequency of exceptionally strong precipitations such as those that occurred during the summer of 1999 in the Douglas Creek catchment which led to a suspension transport of 153 t/km2 and a bedload sediment transport of 443 t/km2 in 12 days. The average annual suspension transport of Andy Creek is 71 t/km2/a, and 353 t/km2/a of Douglas Creek. The average annual solution transport of Andy Creek is 19 t/km2/a, and 51 t/km2/a of Douglas Creek. Including the hardly recordable bed-load transport, the total equivalent surface lowering rate by fluvial sediment trans-port is about 340 mm/1000a in the Andy Creek catchment and 840 mm/1000a in the Douglas Creek catchment area.